Envisioning the financial and psychological hardships of cancer - Rupak Kumar Borah; Bhavana Barman; Hari Kanta Choudhury (Wolters Kluwer Medknow Publications, 2022)
Cancer is one of the leading causes of premature death and disability worldwide. With the progress of the health-care system, the cost of cancer treatment is also rising. Poor households suffer disproportionately from the financial burden of cancer treatment, which has pushed many households into poverty. Thus, cancer poses an economic burden for individuals, families, societies, and governments because of the prolonged medical costs, out-of-pocket expenditures, loss of productivity, and premature deaths. Moreover, the psychological breakdown phenomenon and social implications of cancer play a vital role in dealing with cancer patients. The psychological effect of battling with cancer falls not only on the patient but also on the caregivers and family members. With these backgrounds, an attempt is made in this review paper to highlight the implications of cancer on financial and psychological aspects.